The gospel in the marketplace of ideas : Paul's Mars Hill experience for our pluralistic world - Copan, Paul. (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2014)
Our world ranges from fundamental monotheism to do-it-yourself spirituality to strident atheism. How can Christians engage in communicating across worldviews in this pluralistic and often relativistic society? When Paul visited Athens, he found an equally multicultural and multireligious setting. Copan and Litwak show how Paul's speech to the Athenians provides a practical model for Christians today.
Welcome to Athens -- Was Paul's speech at Athens a mistake? -- Paul's Athens -- Our Athens -- Paul's speech in acts -- Paul's audience -- Paul's gospel for the educated -- The art of persuasion -- Acting on the truth -- Going to our own Mars Hill.
Includes bibliographical references and index.
Keywords: Bible -- Criticism, interpretation, etc; Paul, -- the Apostle, Saint; Athens (Greece) -- Religion; Christianity and other religions; Evangelistic work; Apologetics; Witness bearing (Christianity); Missions